(untitled) (Al-Qamar, 2023)
In Pakistan, the proportion of Persons with Disabilities (PWDs) has significantly risen. This weaker section of society was habitually neglected, exposed to discrimination, put to legal violations, and banned from practically all advanced vocations while disregarding their other abilities for participation in the routine affairs of life. There was no dynamic legislative framework in place and no forward-thinking research to defend the rights of these PWDs in Pakistan. The problems that PWDs are now experiencing appear to be caused by excessive social, physical, and attitudinal action or inaction on the part of society. Therefore, it is essential that Pakistan’s present laws be evaluated from the perspective of international human rights treaties and that administrative measures be put into place at the national level to eliminate the exploitation faced by PWDs. After ratifying the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), Pakistan has built a legislative framework for PWDs, but its efficacy remains unexplored. The article will thoroughly discuss the framework and its efficacy. In discussing PWDs’ rights under the UNCRPD, the article emphasizes the active fundamental liberties that PWDs enjoy. The study will also discuss PWDs’ challenges in Pakistan and the subtle bias that impedes their advancement. Ultimately, it will offer suggestions for improving legislation and implementation mechanisms to advance the welfare of PWDs in Pakistan.